The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/21582440221096445
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Prevention of Big Data Applications: A Systematic Literature Review

Abstract: This paper focuses on privacy and security concerns in Big Data. This paper also covers the encryption techniques by taking existing methods such as differential privacy, k-anonymity, T-closeness, and L-diversity. Several privacy-preserving techniques have been created to safeguard privacy at various phases of a large data life cycle. The purpose of this work is to offer a comprehensive analysis of the privacy preservation techniques in Big Data, as well as to explain the problems for existing systems. The adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…With the proliferation of surveillance technologies and data collection practices, maintaining anonymity and pseudonymity becomes increasingly challenging, as individuals' activities, behaviors, and interactions are continuously monitored, tracked, and analyzed. The erosion of anonymity undermines individuals' ability to control their personal information, protect their privacy, and maintain autonomy over their digital identities (Rafiq, et al, 2022).…”
Section: Escalating Surveillance Landscapementioning
confidence: 99%
“…With the proliferation of surveillance technologies and data collection practices, maintaining anonymity and pseudonymity becomes increasingly challenging, as individuals' activities, behaviors, and interactions are continuously monitored, tracked, and analyzed. The erosion of anonymity undermines individuals' ability to control their personal information, protect their privacy, and maintain autonomy over their digital identities (Rafiq, et al, 2022).…”
Section: Escalating Surveillance Landscapementioning
confidence: 99%
“…For instance, some scholars have been exploring cybersecurity risks in HE (Aliyu et al, 2020; Ulven & Wangen, 2021), while others have proposed interdisciplinary strategies to develop more privacy‐conscious mHealth interventions for the HE community (Blackmon & Lanford, 2023). Others still are exploring how to preserve privacy in Big Data applications (Rafiq et al, 2022) and how the institutional decision to centralise IT decision‐making may impact cybersecurity breaches (Liu et al, 2020). It is against this backdrop that we offer our legal contribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the use of big data systems grows, the capability of attackers to leverage associated parallel computing power for nefarious reasons also increases [3]. A systematic review of 32 papers pertaining to securing big data found that a critical need in future research is building more secure big data infrastructure [4]. Contributing to the latter objective, the researchers demonstrate how varying network architectures impact the security and performance of big data systems.…”
Section: Introductionmentioning
confidence: 99%